The Effects of a Ten Week Training Programme on the Aerobic Power of Football Referees in Malaysia - Nathan, Subramaniam (1995)
The purpose of this study was to investigate the effectiveness and acceptabilty of a ten week aerobic training programme to improve the aerobic power of football referees to enable them to run at least 2600 metres in the Cooper's 12 Minute Test. The study also investigated whether there was any significant difference in the distances covered by the three groups of football referees in the Cooper's 12 Minute Test after ten weeks of training. It evaluated whether there was a significant difference in the two training methods employed in this study. The Cooper's 12 Minute Test was used to measure the aerobic power of the referees. The design of this study focussed upon individual distances covered in the pretest,providing training for ten weeks and determining if referees improved in aerobic power as a result of treatment. Three hypothesis were tested at .05 level of significance. The dependent t-test was used to test hypothesis one. The results indicated that the aerobic power of the subjects in experimental group two improved significantly. All the subjects in experimental group two were able to run more than 2600 metres in the Cooper's 12 Minute Test. ANOVA procedures were used to test hypothesis two. The results ANOVA indicated that there was a significant difference in the distance covered by the three groups of referees in the Cooper's 12 Minute Test after ten weeks of training. The Newman-Kleus method of making multiple comparison indicated that the experimental group two showed the best performance and the control group the poorest in the Cooper's 12 Minute Test. The third hypothesis was tested using the independent t-test. The results indicated that the training method used by the experimental group two was better than the training methods used by the other two groups. All three null hypothesis were rejected.